Measured and estimated discharge and suspended sediment flux of the Chao Phraya River, along with the Phetchaburi, Mae Klong, Tha Chin, and Bang Pakong Rivers during 1912-2020 - Bingbing Wei (PANGAEA, 2025)
This dataset contains river discharge and suspended sediment flux of the Chao Phraya River, along with the Phetchaburi, Mae Klong, Tha Chin, and Bang Pakong Rivers during 1912-2020. The data was obtained from hydrological stations within each river basin, as documented in the Thailand Hydrological Yearbook, and re-analysed to generate average river discharge and suspended sediment flux from 1912 to 2020.